2017
DOI: 10.1111/jce.13319
|View full text |Cite
|
Sign up to set email alerts
|

Ganglionated plexi as neuromodulation targets for atrial fibrillation

Abstract: The autonomic nervous system plays an important role in the genesis of atrial fibrillation and is one of the candidate targets for atrial fibrillation therapy. This review focuses on the role of the autonomic nervous system in atrial fibrillation development and discusses the results of the ganglionated plexi catheter and surgical ablation in preclinical and clinical studies. The heart is innervated by the extrinsic and intrinsic autonomic nervous systems. The intrinsic autonomic nervous system consists of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…Autonomic nervous system and atrial fibrillation The LA contains 4 GPs, which are located at the epicardial aspect of the LA-PV junction. 1 The GPs include both adrenergic and cholinergic nerve fibers that control cardiac A reduction of 25 ms or lower for Δ SDNN at 3 months post-CA was associated with an increase in the prevalence of LRAF from 19.6% to 41% in the ERAF -free patients (n = 85) and from 130 120 110 100 90 80 70 60 50 40 Mean HR, bpm 1400 1300 1200 1100 1000 900 800 700 600 500 Mean R- and 2 denervation after CA and subsequent gradual reinnervation. Of note, despite partial reinnervation after 3 to 6 months after ablation, the HRV markers of the overall sympatho -vagal balance (SDNN, SDSD, pNN50, and mean R -R interval) and more specific HRV indices of parasympathetic activity (rMSSD and LF / HF ratio) were still significantly reduced at 1 year after CPVI in the AF -free patients but not in those with the recurrence of arrhythmia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Autonomic nervous system and atrial fibrillation The LA contains 4 GPs, which are located at the epicardial aspect of the LA-PV junction. 1 The GPs include both adrenergic and cholinergic nerve fibers that control cardiac A reduction of 25 ms or lower for Δ SDNN at 3 months post-CA was associated with an increase in the prevalence of LRAF from 19.6% to 41% in the ERAF -free patients (n = 85) and from 130 120 110 100 90 80 70 60 50 40 Mean HR, bpm 1400 1300 1200 1100 1000 900 800 700 600 500 Mean R- and 2 denervation after CA and subsequent gradual reinnervation. Of note, despite partial reinnervation after 3 to 6 months after ablation, the HRV markers of the overall sympatho -vagal balance (SDNN, SDSD, pNN50, and mean R -R interval) and more specific HRV indices of parasympathetic activity (rMSSD and LF / HF ratio) were still significantly reduced at 1 year after CPVI in the AF -free patients but not in those with the recurrence of arrhythmia.…”
Section: Resultsmentioning
confidence: 99%
“…6 Thus, in younger patients with no evidence of structural heart disease, vagal predominance promotes the triggered PV activity associated with afterdepolarization, shortens the PV refractoriness and AF cycle length, resulting in the inducibility and / or maintenance of AF. 1,11 Outcomes of denervation and ablation for atrial fibrillation The GP ablation led to a vagal response (ie, bradycardia and hypotension) during RF current application, and subsequently to noninducibility of vagally mediated AF. 1 Several studies reported a significant change of the HRV parameters after CPVI, indicating a remarkable parasympathetic withdrawal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations